2018
DOI: 10.1111/ijd.14075
|View full text |Cite
|
Sign up to set email alerts
|

Combined fractional carbon dioxide laser and long‐pulsed neodymium : yttrium‐aluminium‐garnet (1064 nm) laser in treatment of hidradenitis suppurativa; a prospective randomized intra‐individual controlled study

Abstract: Combination of fractional CO laser and long pulsed Nd : YAG (1064 nm) laser in treatment of HS had higher improvement and patient's satisfaction together with lower recurrence compared with long pulsed Nd : YAG (1064 nm) laser alone. Better results could be achieved with low PGA, non-obese populations, and absence of surgeries for the lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 58 publications
(67 reference statements)
0
14
0
1
Order By: Relevance
“…This outcome is somewhat nebulous and may include aspects of long‐term control (free from flares) as well as constructs such as relapse or recurrence. In contrast to flare, the terms recurrence and relapse were used more frequently in the literature and had a higher proportion of studies with a definition (Table S1; see Supporting Information) . Again, in contrast to flare, recurrence or relapse were more frequently associated with an increase in HS activity after a surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…This outcome is somewhat nebulous and may include aspects of long‐term control (free from flares) as well as constructs such as relapse or recurrence. In contrast to flare, the terms recurrence and relapse were used more frequently in the literature and had a higher proportion of studies with a definition (Table S1; see Supporting Information) . Again, in contrast to flare, recurrence or relapse were more frequently associated with an increase in HS activity after a surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Kwon et al 11 found ablative modalities to have superior improvement, less pain, and lower side effects ( P < .05). Robati et al found no significant difference between ablative therapy and nonablative therapy, while Azim et al found statistically significant improvement in combined therapy vs nonablative therapy 4,5 …”
Section: Discussionmentioning
confidence: 99%
“…An appropriate combination of topical, oral and surgical therapy should be used to treat HS depending on the stage of the disease and other patient characteristics. Surgery, 29,30 photodynamic treatment and LASER surgery 31,32 and adalimumab treatment 33 have been reported in a few patients from Egypt and South Africa. A study on combination of surgery and oral retinoids in management of HS has been reported from India 34 …”
Section: Treatmentmentioning
confidence: 99%